Randomized Clinical Trial Comparing Mean Postoperative Pain Score in Hemorrhoidectomy using a Bipolar Vessel Sealing System Ligasure with Conventional open Diathermy Hemorrhoidectomy - Kiran Naz, Amreen A. Razzaque, Misbah Mahmood, Waqas Rind, Farhan Sozera, Areebah Salim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hemorrhoids are one of the most frequent anorectal disorders and are responsible for considerable patient suffering and disability. Excisional hemorrhoidectomy is considered the gold standard1 for grade 3 and 4 haemorrhoids. Milligan Morgan haemorrhoidectomy by LigaSure is being investigated by a number of studies in the literature for its comparison with conventional diathermy method in terms of post-operative pain scores. Many studies favor the use of LigaSure in haemorrhoidectomy while other studies have found conventional methods to be either comparable or even superior to Ligasure. The purpose of this study was to know which method is superior, so that the better method would be preferred over the other one to minimize the post-operative pain, the major cause of post-operative morbidity and also to reduce the post-operative analgesia requirement, an important factor influencing the cost-effectiveness of the proposed method. Objective: To compare mean postoperative pain score in patients undergoing hemorrhoidectomy using Ligasure bipolar vessel sealing system with conventional open diathermy hemorrhoidectomy Methods: Patients aged between 20 to 60 years with symptomatic, third or fourth degree haemorrhoids were included in the study. Randomization to Group A (LigaSure group) or Group B (Diathermy group) was done using sealed envelopes with allocations to either procedure determined just prior to surgery. Perioperative medical treatment was standardized. Operative time was recorded. Patients were inquired about the pain score by using Visual analogue score at 24 hours post-operatively. Numbers of doses of analgesia required in 24 hours were also recorded. Results: Mean age of the patients was 42.05 ± 10.82 years. Study population consisted of 60 % males and 40% females. Mean operative time was significantly lower in Group A (17.10 ± 2.15 min) than Group B (24.63 ± 3.17 min) (P-value ˂ 0.001). Mean VAS score at 24 hours post-operatively was also significantly lower in Group A (2.07± 2.13) versus Group B (4.67± 1.62) (P-value ˂ 0.001). Mean number of doses of analgesia requirement in 24 hours post-operatively was also found to be significantly lower in Group A (0.97± 0.41) compared to Group B (2.17± 0.53) (P-value ˂ 0.001). Conclusion: LigaSure haemorrhoidectomy is significantly better than conventional method of open diathermy haemorrhoidectomy in terms of post-operative pain scores and post-operative analgesia requirement and it can be preferred over the conventional method due to its effect on reducing the morbidity and reducing the cost of analgesia requirement.